Using a liposomal ozone-based solution in comprehensive treatment of bacterial keratitis (Ukrainian Journal of Ophthalmology, 2025)
Background: Keratitis is an inflammatory eye disease frequently leading to complications, significantly decreased vision and visual disability. Common infectious agents include, in particular, aggressive Gram-negative microflora and opportunistic bacteria. The use of conventional antibacterial therapy does not guarantee a positive treatment effect. Infections caused by antibiotic-resistant germs frequently result in increased hospitalization rates with an increased length of inpatient stay at hospital and can cause severe corneal opacities. Formation of biofilms is a cause of increased antibiotic resistance.Purpose: To improve the efficacy of treatment of bacterial keratitis by integrating an adjunctive liposomal ozone-based solution into comprehensive treatment.Material and Methods: Forty-four patients (44 eyes) with bacterial keratitis, aged from 29 to 75 years, were involved in the study. Patients were divided into an ozone group of 21 patients and a control group of 23 patients. All patients were administered antibacterial therapy, mydriatics, desensibilizing agents, tissue preparations and vitamins. In addition, patients of the ozone group received an eye drop of ozone-based solution four times a day for 10 days.Results: The method allowed for a significant (р < 0.001) reduction in conjunctival discharge, mixed conjunctival injection, corneal edema and inflammatory response, leeading to a 3.3 ± 0.1 day reduction in the length of inpatient stay at the hospital.Conclusion: Utilizing a liposomal ozone-based solution as an adjunct to the comprehensive treatment of bacterial keratitis is a novel treatment method making it possible to accelerate corneal epithelization and reduction in inflammation, and to shorten the length of treatment.
Keywords: bacterial keratitis; liposomal ozone-based solution; comprehensive treatment; clinical scores